Identification of CYP2B6 as a principal human enzyme involved in the metabolic bioactivation of chlorfenapyr to tralopyril - Zengzhen Wei; Decai Cao; Jing Zhang; Gen Ba; Beiyan Zhang; Chufan Liu; Hao Sun; Feng Chen; Jinsong Zhang; Zhengsheng Mao (Pesticide Biochemistry and Physiology, 2026)

Enriched numerical manifold method with closed-form solutions for the crack-tip singularity in elastic fracture - Hua-rui ZHU; Hong ZHANG; Xi-long LI; Wei WU; Sun-jun HU; Gen-hua SHI (Computers and Geotechnics, 2026)

A Phase Field Model for Rock Fracture Based on the Modified Mohr–Coulomb Failure Criterion - Mingtao Zhang; Gen Li; Guang Han; Laigui Wang; Xiangfeng Liu; Qi Sun; Chuang Sun; Jinyang Du (Rock Mechanics and Rock Engineering, 2026)

Tectonically driven erosion with climatic modulation across the southern Tibetan Plateau: Insights from 10Be erosion rates - Jia-Qi Sun; Jin-Gen Dai; Xu Han; Matthew Fox; Guang-Sheng Ren; Zhi-Cheng Yu; Bo-Rong Liu; Xiang-Rui Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mitochondria-targeted redox-logic carbon dots for in vivo realtime visualization of peroxynitrite during wound-healing - Jing-Yu Hu; Xin Gen; Yuan-Qiang Sun; Zhao-Hui Li (Analytica Chimica Acta, 2026)

Theta-aurora dynamics: Ionospheric mapping of evolving magnetospheric plasma boundaries - Xin-Ming Chen; Zan-Yang Xing; Qing-He Zhang; Yong-Liang Zhang; Hui-Gen Yang; L. R. Lyons; K. Oksavik; S. E. Milan; Rui-Long Guo; Tong Xu; Bin-Bin Tang; Xiang-Yu Wang; et al. (Science China Earth Sciences, 2026)
The theta-aurora, an auroral feature bridging the nightside and dayside auroral oval under a northward interplanetary magnetic field (IMF), is closely linked to the energetic plasma evolving within the magnetosphere. While existing views emphasize that energetic plasma resides on closed field lines, the mechanism by which it is accelerated and precipitates on open field lines to form the theta aurora remains poorly understood. Here, we introduce a mechanism derived from multi-instrument observations of theta-aurora evolution in the Northern Hemisphere and simulations conducted using a global magnetohydrodynamics (MHD) model. The observations and simulations exhibit excellent agreement, revealing that the theta-aurora represents ionospheric projections of boundaries between distinct magnetospheric plasma. These different magnetospheric plasma, an energetic structure originating from the plasma sheet and the preexisting cold lobe plasma, develop a boundary with contrasting physical properties that drive localized plasma instabilities. Particle precipitation occurs at plasma boundary, and controls both the formation and temporal evolution of theta-aurora. Our findings provide critical insights into the coupling between the ionosphere and magnetosphere under northward IMF.

CRISPR/Cas9-mediated mstnb knockout enhances muscle growth in salt-tolerant tilapia - Zituo Yang; Le Wang; Fei Sun; Joey Wong; May Lee; Gen Hua Yue (Aquaculture, 2026)

Magmatic source effects on Zircon Eu anomalies: Refining the Late Cretaceous–Eocene uplift of the Gangdese Arc, Southern Tibet - Guang-Sheng Ren; Jin-Gen Dai; Xiang-Rui Liu; Xu Han; Bo-Rong Liu; Jia-Qi Sun (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Adipose tissue-secreted Igf2 during promoting adipocyte hyperplasia improves muscle texture caused by high-fat diet through inhibiting myostatin in grass carp (Ctenopharyngodon idellus) - Zhiqi Tian; Handong Li; Mingkui Wei; Hong Ji; Gen He; Jian Sun (Aquaculture, 2026)

Multiscale Numerical and Experimental Evaluation of Microindentation Tests for Characterizing the Strength and Failure Mechanisms of Black Shale - Xiaoning Li; Enjian Wu; Wu Bo; Gen Zhang; Gopi Krishna Basyal; Sixiang Ling; Tangyao Wang; Chunwei Sun (Rock Mechanics and Rock Engineering, 2026)

Electrostimulation enhances nitrate removal and mitigates nitrite accumulation from denitrification-induced alkalization - Yulong Wang; Daxin Sun; Yongheng Zhan; Nan Chen; Weiwu Hu; Gen Wang; Chuanping Feng; Shuang Tong (Environmental Research, 2026)

A high-strength, heat-resistant, recyclable, and degradable ramie fiber-reinforced polyimine biocomposite - Pandeng Li; Tingting Liu; Gen Lu; Tong Shu; Tianyi Yu; Yuchen Zhao; Hengwei Fu; Junqi Yang; Haoping Du; Penghao Sun; Ziqi Hou; Chunhua Fu; et al. (Chemical Engineering Journal, 2026)

Green hydrogen production and potential evaluation via chemical looping reforming of pyrolytic volatiles from reed - Chunyu Cheng; Zhongshun Sun; Huili Huang; Gen Liu; Meixin Li; Chen Song; Bolun Yang; Zhiqiang Wu (Fuel, 2026)

Hierarchical acceptor engineering of NIR-II butterfly aggregation-induced emission luminogens for enhanced theranostic efficiency - Cheng Lu; Zonghang Liu; Mengli Liu; Zihao Huang; Jianwei Sun; Ryan T.K. Kwok; Tie-Gen Chen; Jacky W.Y. Lam; Ben Zhong Tang (Chemical Engineering Journal, 2026)

Mutations Upstream of ppp2ca Affect Body Weight in Asian Seabass - Joey Wong; Shadame Yeo; Tung-Hsuan Tsai; Yixuan Tay; Zituo Yang; Le Wang; Fei Sun; May Lee; Yanfei Wen; Hongyan Pang; Gen Hua Yue (Marine Biotechnology, 2025)

Numerical Simulation and Tests of Lateral Bearing Capacity of Sloped Offshore Monopile Under Vertical Load and Lateral Cyclic Load - Yongqing Lai; Gen Xiong; Ben He; Yilong Sun; Lin Guo; Kaiyuan Liu (Journal of Marine Science and Engineering, 2025)
Offshore monopile foundations endure complex loads during service. They bear vertical loads from the superstructure’s self-weight and lateral cyclic loads (e.g., wind, waves), while near-coastal seabeds are usually sloped. To resolve these issues, model pile tests under combined vertical and lateral cyclic loads were carried out to study how slope angle and vertical load affect monopile deformation. A numerical model was validated via comparison with test results and then used to reveal the development of cumulative deformation in offshore sloped monopiles under the above combined loads. The results show that, below 1000 cycles, the cumulative displacement of the pile increases logarithmically with the number of cycles. As the slope angle increases, the cumulative deformation increases. In these tests, the cumulative deformation of the pile increases by 114% compared to the results of the flat site, but it decreases with an increase in vertical load. As such, when a 3 N vertical load is applied to the pile top, its deformation at the flat site decreases by 20%, but its deformation at a 20° slope site decreases by 10%. Finally, a predicted formula is proposed for offshore monopiles with the effect of slope angle, and this formula can provide a preliminary assessment method of cumulative.

A new insight into the mechanism of DEHP-induced cardiotoxicity: Triggering pyroptosis of cardiomyocytes by disrupting sphingolipid metabolism - Jia-Gen Cui; Hao Zhang; Yue-Qi Zhang; Bing Sun; Xue-Nan Li; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Electrically conductive and anti-inflammatory nerve conduits based on chitosan/hydroxyethyl cellulose hydrogel for enhanced peripheral nerve regeneration - Jiahui Song; Chenlong Liao; Zhengchao Yuan; Xiao Yu; Jie Cui; Yangfan Ding; Panpan Shang; Jinglei Wu; Binbin Sun; Mohamed EL-Newehy; Meera Moydeen Abdulhameed; Wenchuan Zhang; et al. (Carbohydrate Polymers, 2025)

Integrating methane conversion with multi-pathway nitrogen removal for wastewater in membrane-enabled stratified biofilm: System development and microbial dynamics - Chun-Yan Yuan; Yu-Xia; Jia-Hao Huo; Cai-Long Nie; Ke-Xin Zhang; Liang-Feng; Xiao-Li Su; Zi Song; Gen-Ping Yi; Fei-Yun Sun (Bioresource Technology, 2025)

Four new fluorenones isolated from the mycelia of medicinal mushroom Piptoporus soloniensis (Dubois:Fr.) Pilat and their anti-inflammatory activity - Lan Yao; Yi-Fan Sun; Ren-Ya Ji; Zi-Chen Tian; Shu-Han Zhang; Gen-Wei Zhang; Jian-Hua Lv (Natural Product Research, 2025)

Complete genome sequence of Lysinibacillus sp. WB86, a potential antimicrobial lanthipeptides producer - Huai-Ying Sun; Ji-Xiang Xin; Gen Li; Zhen-Yi Zhou; Xin Li; Hong Wang; Qun-Jian Yin; Bin Wei (Marine Genomics, 2025)

Computational design and efficacy assessment of Bufalin-Dendrimer nanoformulation for enhanced cancer therapy - Yurong Sun; Yinhua Lin; Huaitao Sun; Junfa Yang; Hui Cheng; Jia Yi; Wenqiang Li; Gen Lu; Cheng Zhao; Yuge Jiang; Xinyu Zhao; Qinglin Li; et al. (Chemical Engineering Journal, 2025)

Oxygenated volatile organic compounds in Beijing: Characteristics, chemical reactivity, and source identification - Gen Zhang; Xiaoqi Zhou; Yifeng Sun; Chong Han; Jiyun Xian; Changxu Mu; Wanyun Xu; Linlin Liang (Environmental Pollution, 2025)

Promoting adipocyte hyperplasia ameliorates high-carbohydrate diet-induced inflammation, oxidative stress, and metabolic disorders and enhances growth performance and immune function in grass carp (Ctenopharyngodon idellus) - Mingkui Wei; Zhiqi Tian; Niankun Zhang; Lu Zhou; Handong Li; Hong Ji; Gen He; Jianlu Zhang; Jian Sun (Fish Physiology and Biochemistry, 2025)

The Enhancing Effect of the East Asian Subtropical Westerly Jet on Summer Extreme High-Temperature Events over Central-Eastern China Since the Late 1990s - Chujie Gao; Yuyu Niu; Gen Li; Shanlei Sun; Bo Lu; Chaofan Li; Bei Xu; Jinglong Huang; Xiubao Sun (Advances in Atmospheric Sciences, 2025)

Salt tolerance candidate genes identified by QTL mapping, RNA-seq, and functional analysis in tilapia - Zituo Yang; Le Wang; Fei Sun; Joey Wong; May Lee; Shadame Yeo; Yanfei Wen; Gen Hua Yue (Aquaculture, 2025)

Mapping the genetic basis for sex determination and growth in hybrid tilapia (Oreochromis mossambicus × O. niloticus) - Le Wang; Fei Sun; Zituo Yang; May Lee; Shadame Yeo; Joey Wong; Yanfei Wen; Gen Hua Yue (Aquaculture, 2024)

Docosahexaenoic acid (DHA) regulates mitochondrial quality control via MEK/ERK activation to promote myoblast-to-myotube formation in grass carp (Ctenopharyngodon idellus) - Shanghong Ji; Chenchen Bian; Jian Sun; Handong Li; Gen Kaneko; Hong Ji (Aquaculture, 2024)

Matrine inhibits invasion and migration of gallbladder cancer via regulating the PI3K/AKT signaling pathway - Rong-Liang Mo; Zhuang Li; Peng Zhang; Ming-Hui Sheng; Gen-Cheng Han; Deng-Qun Sun (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Impacts of feeding three strains of microalgae alone or in combination on growth performance, protein metabolism, and meat quality of broiler chickens - Tao Sun; Sahil Kalia; Benjamin M. Wyman; Keith J. Ou; Xin Gen Lei (Algal Research, 2024)

A Method for Estimating the Distribution of Trachinotus ovatus in Marine Cages Based on Omnidirectional Scanning Sonar - Yu Hu; Jiazhen Hu; Pengqi Sun; Guohao Zhu; Jialong Sun; Qiyou Tao; Taiping Yuan; Gen Li; Guoliang Pang; Xiaohua Huang (Journal of Marine Science and Engineering, 2024)
In order to accurately estimate the distribution of Trachinotus ovatus in marine cages, a novel method was developed using omnidirectional scanning sonar and deep-learning techniques. This method involved differentiating water layers and clustering data layer by layer to achieve precise location estimation. The approach comprised two main components: fish identification and fish clustering. Firstly, omnidirectional scanning sonar was employed to perform spiral detection within marine cages, capturing fish image data. These images were then labeled to construct a training dataset for an enhanced CS-YOLOv8s model. After training, the CS-YOLOv8s model was used to identify and locate fish within the images. Secondly, the cages were divided into water layers with depth intervals of 40 cm. The identification coordinate data for each water layer were clustered using the DBSCAN method to generate location coordinates for the fish in each layer. Finally, the coordinate data from all water layers were consolidated to determine the overall distribution of fish within the cage. This method was shown, through multiple experimental results, to effectively estimate the distribution of Trachinotus ovatus in marine cages, closely matching the distributions detected manually.

Donor polarization engineering of conjugated microporous polymers to boost exciton dissociation for photocatalytic degradation of tetracycline - Zhaozhang Deng; Weijie Zhang; Penghao Sun; Hongwei Zhao; Xinxiu Cao; Gen Li; Shaohui Xiong; Qingquan Liu (Chemosphere, 2024)

Iodine/soluble starch cryogel: An iodine-based antiseptic with instant water-solubility, improved stability, and potent bactericidal activity - Wei Sun; Zi-Xi Wang; Yuxin Guo; Chengcheng Li; Ge Gao; Fu-Gen Wu (Carbohydrate Polymers, 2024)

Water flush boosts performance of elemental sulfur-based denitrification packed-bed systems: Optimization and mechanisms - Jia-Min Xu; Heng Dong; Hao-Ran Xu; Yi-Lu Sun; Yang Yu; Li-Ying Zhang; Gen-Ping Yi; Wen-Ke He; Chang-Min Wu; Ai-Jie Wang; Hao-Yi Cheng (Bioresource Technology, 2024)

Sustainable release of borate- and nitrate- electrolyte additives via metal-organic frameworks nanocapsules for stable lithium metal batteries - Jiaxing Yan; Jiaqi Li; Wenqiang Fang; Yuanhang Gao; Zuosu Qin; Mingwei Sun; Ying Zhang; Ning Zhang; Xiaohe Liu; Gen Chen (Chemical Engineering Journal, 2024)

Variation characteristics of fluorescent biological aerosol particles in Beijing under springtime clean, haze and dusty condition - Linlin Liang; Wanyun Xu; Chang Liu; Xuyan Liu; Hongbing Cheng; Yusi Liu; Gen Zhang; Yangmei Zhang; Junying Sun (Urban Climate, 2024)

Fabrication of stable spherical soybean lipophilic protein nanogel for curcumin delivery: Carbony oxygen and aromatic ring flexibility binding to the beta−barrel - Jianhua Zeng; Junzhe Zou; Lanwei Zhang; Jinlong Zhao; Linlin Liu; Gen Lu; Bingyu Sun; Yanguo Shi; Xiuqing Zhu; Pimin Gong (Food Structure, 2024)

Molecular mapping of QTL for rice black-streaked dwarf disease resistance in rice (Oryza sativa L.) - Zhiguang Sun; Gen Pan; Hongzhou An; Baoxiang Wang; Dayong Xu (Cereal Research Communications, 2024)
Rice black-streaked dwarf disease (RBSDD) is one of the most serious crop diseases in Asia, causing serious damage to rice production. Therefore, reducing the harmful effects of RBSDD is vital to the food security of China and other Asian countries. In this study, 248 rice varieties from different countries were screened for resistance to RBSDD, and 19 varieties with high resistance to RBSDD were found. Among them, H185, an indica variety, showed stable and high resistance to RBSDD. Using an F 2:3 population of H185 and Wuyujing 3 (WYJ3, a highly susceptible japonica rice variety), three QTL conferring resistance to RBSDD, namely qRBSDD2 , qRBSDD7 , and qRBSDD11 were identified, and they explained 53.6% of the total phenotypic variation. Among them, qRBSDD2 and qRBSDD7 , with LOD scores of 4.26 and 4.25, respectively, were repeatedly detected in artificial inoculation conditions, accounting for 28.0% and 29.8% of the total phenotypic variation, respectively. Resistant alleles of the two QTL were all derived from H185, and several BC 5 F 2 lines possessing single or two QTL of qRBSDD2 and qRBSDD7 exhibited higher resistance for RBSDD. The QTL detected in our study open new possibilities for breeding rice cultivars with RBSDD resistance through resistance gene pyramiding.

Tbx21 gene and its association with resistance against viral nervous necrosis (VNN) in Asian seabass, Lates calcarifer - Joey Wong; Zituo Yang; Le Wang; Fei Sun; Gen Hua Yue (Marine Life Science & Technology, 2024)

Long-term variations in surface ozone at the Longfengshan Regional Atmosphere Background Station in Northeast China and related influencing factors - Xiaoyi Zhang; Jingmin Sun; Weili Lin; Wanyun Xu; Gen Zhang; Yanling Wu; Xin Dai; Jinrong Zhao; Dajiang Yu; Xiaobin Xu (Environmental Pollution, 2024)

Eicosapentaenoic acid (EPA) improves grass carp (Ctenopharyngodon idellus) muscle development and nutritive value by activating the mTOR signaling pathway - Handong Li; Shanghong Ji; Xiangtong Yuan; Yunhe Li; Gen Kaneko; Jian Sun; Hong Ji (Fish Physiology and Biochemistry, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

Efficient capture of iodine in steam and water media by hydrogen bond-driven charge transfer complexes - Li Zhang; Yu-Ting Luo; Jia-Qi Fan; Sai-Jin Xiao; Qiong-Qing Zheng; Xiao-Lin Liu; Quan-Gen Tan; Chen Sun; Qiang Shi; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2024)

Severe photochemical pollution formation associated with strong HONO emissions from dew and guttation evaporation - Wanyun Xu; Ye Kuang; Chang Liu; Zhiqiang Ma; Xiaoyi Zhang; Miaomiao Zhai; Gen Zhang; Weiqi Xu; Hongbing Cheng; Yusi Liu; Biao Xue; Biao Luo; et al. (Science of The Total Environment, 2024)

Unveiling the underwater threat: Exploring cadmium's adverse effects on tilapia - Zituo Yang; Joey Wong; Le Wang; Fei Sun; May Lee; Gen Hua Yue (Science of The Total Environment, 2024)

Non-cytochrome P450 enzyme aldehyde oxidase is involved in the oxidative metabolic pathway of diquat and its detoxification effect - Zhengsheng Mao; Youjia Yu; Gen Ba; Hongmei Zhao; Qifang Shi; Yue Cao; Weiran Xie; Jinsong Zhang; Hao Sun; Feng Chen (Pesticide Biochemistry and Physiology, 2024)

The Antidepressant Effect of Magnolol on Depression-Like Behavior of CORT-Treated Mice - Chi Xu; Jiayu Ye; Yanting Sun; Xiujian Sun; Jing-gen Liu (Journal of Molecular Neuroscience, 2024)

Docosahexaenoic acid (DHA) alleviates hepatic lipid accumulation by regulating mitochondrial quality control through ERK signaling pathway in grass carp (Ctenopharyngodon idellus) - Chenchen Bian; Shanghong Ji; Caihong Zeng; Jian Sun; Gen Kaneko; Hong Ji (Aquaculture, 2024)

Lcalmnb2: Asian seabass gene involved in resisting SGIV - Yepin Yu; Zituo Yang; Le Wang; Fei Sun; May Lee; Gen Hua Yue (Aquaculture, 2024)

Docosahexaenoic acid (DHA) promotes grass carp (Ctenopharyngodon idella) muscle fiber development by activating MEK/ERK pathway in vitro and in vivo - Shanghong Ji; Handong Li; Xiaocheng Huang; Jian Sun; Gen Kaneko; Hong Ji (Aquaculture, 2024)

Transposon insertion into pmel-17 reduced melanin pigmentation, and growth, but increased locomotion of Mozambique tilapia - Le Wang; Fei Sun; Zituo Yang; Yepin Yu; Yanfei Wen; Gen Hua Yue (Aquaculture, 2024)

Methionine deficiency affects myogenesis and muscle macronutrient metabolism in juvenile turbot Scophthalmus maximus - Zhongmin Sui; Xuan Wang; Yongkai Sun; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Aquaculture, 2024)

Degradation of aqueous phenol by combined ultraviolet and electrochemical oxidation treatment - Hongxiang Xu; Xin Sun; Han Yang; Jiahua Cui; Jingzheng Wang; Yuntao Kang; Jiushuai Deng; Gen Huang (Journal of Cleaner Production, 2024)

A benchmark study for quasi-static numerical upscaling of seismic wave attenuation and dispersion in fractured poroelastic rocks - Meng-Fan Zhang; Yan-Xiao He; Shang-Xu Wang; Gen-Yang Tang; Chao Sun (Computers & Geosciences, 2023)

Dynamic process and dynamic-stall phenomenon on blade sections of a floating horizontal-axis wind turbine caused by the platform's pitch motion - Zanyang He; Gen Li; Lei Duan; Qinghong Sun (Ocean Engineering, 2023)

Improved biomass burning pollution in Beijing from 2011 to 2018 - Linlin Liang; Zhenyu Du; Guenter Engling; Xuyan Liu; Wanyun Xu; Chang Liu; Yuan Cheng; Dongsheng Ji; Gen Zhang; Junying Sun (Atmospheric Environment, 2023)

pomc knockout increases growth in zebrafish - Zituo Yang; Joey Wong; Le Wang; Fei Sun; Gen Hua Yue (Aquaculture, 2023)

Establishment of a novel signature to predict prognosis and immune characteristics of pancreatic cancer based on necroptosis-related long non-coding RNA - Yuanpeng Xiong; Xiaoyu Kong; Kang Fang; Gen Sun; Shuju Tu; Yongyang Wei; Yonghao Ouyang; Renhua Wan; Weidong Xiao (Molecular Biology Reports, 2023)

Identifying the O3 chemical regime inferred from the weekly pattern of atmospheric O3, CO, NOx, and PM10: Five-year observations at a center urban site in Shanghai, China - Gen Zhang; Yifeng Sun; Wanyun Xu; Lingyan Wu; Yuseng Duan; Linlin Liang; Yuan Li (Science of The Total Environment, 2023)

Spatiotemporal variation of ecological environment quality and extreme climate drivers on the Qinghai-Tibetan Plateau - Tao Sun; Yan-mei Yang; Ze-gen Wang; Zhi-wei Yong; Jun-nan Xiong; Guo-li Ma; Jie Li; Ao Liu (Journal of Mountain Science, 2023)

Experimental study on the movement law of overlying rock non-pillar coal overhead mining - Yong Li; Jing Zheng; Feng-nian Wang; Xin-gen Ma; Rui-xue Zhang; Ying-ying Sun; Jian-bin Yin; Zhi-gang Tao (Journal of Mountain Science, 2023)

Protective effects of egg yolk immunoglobulins (IgY) against CyHV-2 infection in gibel carp (Carassius gibelio) - Bing-Yao Sun; Hai-Yan Kou; Pan-Yang Jian; Ling-Jiao Kong; Jie Fang; Peng-Kun Meng; Kang Wu; Cai-Gen Yang; Gang Yang; Xue-Hong Song (Aquaculture, 2023)

Intelligent shielding material based on VO2 with tunable near-field and far-field electromagnetic response - Si-Yuan Liao; Xiao-Yun Wang; Hai-Peng Huang; Yu-Ying Shi; Qiao-Feng Wang; You-Gen Hu; Peng-Li Zhu; Rong Sun; Ching-Ping Wong; Yan-Jun Wan (Chemical Engineering Journal, 2023)

Optimal dietary methionine requirement of sub-adult turbot (Scophthalmus maximus L.): Growth performance, feed utilization and hepatic lipid metabolism - Zhongmin Sui; Xuan Wang; Yongkai Sun; Huihui Zhou; Chengdong Liu; Kangsen Mai; Gen He (Aquaculture, 2023)

Method for analyzing the evolution characteristics of in-situ stress field considering rheology and degradation: A deeply incised valley in Qinghai-Tibet Plateau, case study - Xiang Sun; Guoqing Chen; Minyao Huang; Shishu Zhang; Jingxi Yang; Jin'gen Ma (Engineering Geology, 2023)

Genomic resources and their applications in aquaculture of Asian seabass ( Lates calcarifer ) - Gen Hua Yue; Le Wang; Zituo Yang; Fei Sun; Yi Xuan Tay; Joey Wong; Shadame Yeo (Reviews in Aquaculture, 2023)
Genomic resources, including nuclear DNA markers, mitochondrial DNA markers, high‐resolution linkage maps, transcriptomes, reference genome sequences and their annotations, are critically important in aquaculture. Their potential applications are plenty, such as enabling the analysis of genetic diversity in population structures, mating and spawning behaviour; genetic traceability; reconstructing pedigrees; mapping quantitative trait loci (QTL) for important phenotypic traits; marker‐assisted selection and genomic selection; and to understand genetic and epigenetic regulation of traits. Asian seabass ( Lates calcarifer ) is becoming a popular aquaculture species. In the past 30 years, many genomic resources have been developed and used to understand the genetic diversity of wild and cultured populations, setting up mating schemes, genetic traceability, mapping QTL and genome‐wide association studies for growth, omega‐3 fatty acid content, resistance to diseases and genetic improvement of important traits in breeding programmes. In this review, we systematically synthesize the status of available genomic resources and their applications in enhancing the genetic improvement and aquaculture production of Asian seabass. We also critically discuss the challenges and future research directions of developing, optimizing and applying genomic resources in Asian seabass aquaculture.

The effect of nitrite and nitrate treatment on growth performance, nutritional composition and flavor-associated metabolites of grass carp (Ctenopharyngodon idella) - Jun-Ming Zhang; Bing Fu; Yi-chao Li; Jin-Hui Sun; Jun Xie; Guang-Jun Wang; Jing-Jing Tian; Gen Kaneko; Er-Meng Yu (Aquaculture, 2023)

Characterization of pIgR and its association with resistance to iridovirus in Asian seabass - Yi Xuan Tay; Yepin Yu; Zituo Yang; Le Wang; Fei Sun; Gen Hua Yue (Aquaculture, 2023)

A modified TOPMODEL introducing the bedrock surface topographic index in Huangbengliu watershed, China - An-ni Qiu; Yan-jun Zhang; Gen-xu Wang; Jun Cui; Yuan-xin Song; Xiang-yang Sun; Li Chen (Journal of Mountain Science, 2022)

The ornamental fighting fish is the next model organism for genetic studies - Gen Hua Yue; Le Wang; Fei Sun; Zituo Yang; Yubang Shen; Zining Meng; Yuzer Alfiko (Reviews in Aquaculture, 2022)
The fighting fish Betta splendens is a freshwater species from Thailand and other Southeast Asian countries. This fish has been domesticated for 1000 years and bred for fighting, various colours, body size and fin types for 600 years. It is one of the most important fish species cultured for the world ornamental fish market. This fish is easy to culture, highly fecund and displays great morphological diversity. Its biology has been studied for over 100 years. Recently, its compact genome and transcriptomes have been sequenced. Genome editing with CRISPR/cas9 has been applied to knock out genes in this fish. Its diverse phenotypes, including colours, colour patterns, fin types, and aggressive behaviour, are complementary to those of other model animals. Therefore, this fish could be the next important model organism for studying phenotypic variation and aggressive behaviour. In this paper, we synthesized knowledge about its aquaculture, biology, genetics, genomic tools, phenotypes and novel insights on phenotypic variation, sex determination and aggression. We hope that the information described in this paper will facilitate genetic studies on phenotypic variations in aquaculture and aggressive behaviour in other species, including humans.

The Insertion in the 3′ UTR of Pmel17 Is the Causal Variant for Golden Skin Color in Tilapia - Feng Liu; Fei Sun; Gang Qiao Kuang; Le Wang; Gen Hua Yue (Marine Biotechnology, 2022)

Orexin A peptidergic system: comparative sleep behavior, morphology and population in brains between wild type and Alzheimer’s disease mice - Peng Zhao; Yaqian You; Zhe Wang; Yanjun Zhou; Gaoshang Chai; Gen Yan; Zhewu Jin; Qing Wang; Hongxu Sun (Brain Structure and Function, 2022)
Sleep disturbance is common in patients with Alzheimer’s disease (AD), and orexin A is a pivotal neurotransmitter for bidirectionally regulating the amyloid-β (Aβ) deposition of AD brain and poor sleep. In the present study, we examined the characteristic of sleep–wake architecture in APPswe/PSldE9 (APP/PS1) and Aβ-treated mice using electroencephalogram (EEG) and electromyographic (EMG) analysis. We compared the expression of orexin A, distribution, and morphology of the corresponding orexin A-positive neurons using innovative methods including three-dimensional reconstruction and brain tissue clearing between wild type (WT) and APP/PS1 mice. Results from our study demonstrated that increased wakefulness and reduced NREM sleep were seen in APP/PS1 and Aβ treated mice, while the expression of orexin A was significantly upregulated. Higher density and distribution of orexin A-positive neurons were seen in APP/PS1 mice, with a location of 1.06 mm–2.30 mm away from the anterior fontanelle compared to 1.34 mm–2.18 mm away from the anterior fontanelle in WT mice. These results suggested that the population and distribution of orexin A may play an important role in the progression of AD.

Linking hydraulic geometry, land use, and stream water quality in the Taihu Basin, China - Yaoyi Liu; Hongju Zhang; Peng Zeng; Yukun Wang; Gen Li; Fengyun Sun; Yue Che (Environmental Monitoring and Assessment, 2021)

Effects of Ocean Acidification on Transcriptomes in Asian Seabass Juveniles - Le Wang; Fei Sun; Yanfei Wen; Gen Hua Yue (Marine Biotechnology, 2021)

Genome-wide association analysis of fiber fineness and yield in ramie (Boehmeria nivea) using SLAF-seq - Kunyong Huang; Yaliang Shi; Gen Pan; Yicheng Zhong; Zhimin Sun; Juan Niu; Jing Chen; Jianhua Chen; Mingbao Luan (Euphytica, 2021)

Systemic effect of dietary lipid levels and α-lipoic acid supplementation on nutritional metabolism in zebrafish (Danio rerio): focusing on the transcriptional level - Chen-cui Huang; Jian Sun; Hong Ji; Gen Kaneko; Xing-da Xie; Zhi-guang Chang; Wei Deng (Fish Physiology and Biochemistry, 2020)

Mixed secondary chromatin structure revealed by modeling radiation-induced DNA fragment length distribution - Wenzong Ma; Chenyang Gu; Lin Ma; Caoqi Fan; Chao Zhang; Yujie Sun; Cheng Li; Gen Yang (Science China Life Sciences, 2020)

Exploring the influence of environmental factors in partitioning evapotranspiration along an elevation gradient on Mount Gongga, eastern edge of the Qinghai-Tibet Platea, China - Ju-ying Sun; Xiang-yang Sun; Zhao-yong Hu; Gen-xu Wang (Journal of Mountain Science, 2020)

Isorhamnetin attenuates Streptococcus suis virulence by inhibiting the inflammatory response - Gen Li; Guizhen Wang; Shuang Wang; Meiyang Sun; Zhongmei Wen (Antonie van Leeuwenhoek, 2020)

Design, synthesis and antifungal activities of novel pyrrole- and pyrazole-substituted coumarin derivatives - Shu-Guang Zhang; Chao-Gen Liang; Yue-Qing Sun; Peng Teng; Jia-Qun Wang; Wei-Hua Zhang (Molecular Diversity, 2019)

Mapping and Validating QTL for Fatty Acid Compositions and Growth Traits in Asian Seabass - Le Wang; Elaine Chua; Fei Sun; Zi Yi Wan; Baoqing Ye; Hongyan Pang; Yanfei Wen; Gen Hua Yue (Marine Biotechnology, 2019)

Influence of High Relative Humidity on Secondary Organic Carbon: Observations at a Background Site in East China - Linlin Liang; Guenter Engling; Yuan Cheng; Xiaoye Zhang; Junying Sun; Wanyun Xu; Chang Liu; Gen Zhang; Hui Xu; Xuyan Liu; Qianli Ma (Journal of Meteorological Research, 2019)

Exogenous application of gibberellic acid and ascorbic acid improved tolerance of okra seedlings to NaCl stress - Yong-Hui Wang; Gen Zhang; Yuan Chen; Jin Gao; Yan-Ru Sun; Ming-Fa Sun; Jian-Ping Chen (Acta Physiologiae Plantarum, 2019)

Total and available metal concentrations in soils from six long-term fertilization sites across China - Dong-Xing Guan; Fu-Sheng Sun; Guang-Hui Yu; Matthew L. Polizzotto; Yun-Gen Liu (Environmental Science and Pollution Research, 2018)

The FTO Gene Is Associated with Growth and Omega-3/-6 Ratio in Asian Seabass - Fei Sun; Rongjian Tu; Jun Hong Xia; Xiao Jun Liu; Gen Hua Yue (Marine Biotechnology, 2018)

Rebirth after death: forest succession dynamics in response to climate change on Gongga Mountain, Southwest China - Gen-wei Cheng; Xu-yang Lu; Xiao-dan Wang; Jian Sun (Journal of Mountain Science, 2018)

Photosynthetic response of Bangia fuscopurpurea (Bangiales, Rhodophyta) towards dehydration and hyposalinity - Wen Jun Wang; Zong Gen Shen; Xiu Tao Sun; Fu Li Liu; Zhou Rui Liang; Fei Jiu Wang; Jian Yi Zhu (Biologia, 2018)

Ground bryophytes regulate net soil carbon efflux: evidence from two subalpine ecosystems on the east edge of the Tibet Plateau - Shou-Qin Sun; Tao Liu; Yan-Hong Wu; Gen-Xu Wang; Bo Zhu; Thomas Henry DeLuca; Yan-Qiang Wang; Ji Luo (Plant and Soil, 2017)

Climate conditions and relative abundance of C3 and C4 vegetation during the past 40 ka inferred from lake sediments in Wudalianchi, northeast China - Gen Wang; Yongli Wang; Zhifu Wei; Baoxiang Wu; Zixiang Wang; Zepeng Sun; Liang Xu; Youxiao Wang (Journal of Paleolimnology, 2017)

Effect of climate change on seasonal water use efficiency in subalpine Abies fabri - Xiang-yang Sun; Gen-xu Wang; Mei Huang; Zhao-yong Hu; Chun-lin Song (Journal of Mountain Science, 2017)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Cochliomycin A inhibits the larval settlement of Amphibalanus amphitrite by activating the NO/cGMP pathway - Kai-Ling Wang; Gen Zhang; Jin Sun; Ying Xu; Zhuang Han; Ling-Li Liu; Chang-Lun Shao; Qing-Ai Liu; Chang-Yun Wang; Pei-Yuan Qian (Biofouling, 2016)

Heat stress impairs mice granulosa cell function by diminishing steroids production and inducing apoptosis - Man Luo; Lian Li; Cheng Xiao; Yu Sun; Gen-Lin Wang (Molecular and Cellular Biochemistry, 2016)

Unveiling equal importance of two 14‐3‐3 proteins for morphogenesis, conidiation, stress tolerance and virulence of an insect pathogen - Qian Liu; Jin‐Gen Li; Sheng‐Hua Ying; Juan‐Juan Wang; Wen‐Liang Sun; Chao‐Guang Tian; Ming‐Guang Feng (Environmental Microbiology, 2015)
Summary Two conserved 14‐3‐3 proteins orthologous to S accharomyces cerevisiae Bmh 1/2 are poorly understood in filamentous fungi. Here we show that Bmh 1 and Bmh 2 contribute equally to the fundamental biology and physiology of B eauveria bassiana by targeting many sets of proteins/enzymes. Single Bmh deletion caused similar upregulation of another. Excellent knockdown (∼91%) expressions of Bmh 1 in Δ Bmh 2 and Bmh 2 in Δ Bmh 1 resulted in equally more severe multiphenotypic defects than the single deletions, including G 2 / M transition, blastospore size, carbon/nitrogen utilization, conidiation, germination and conidial tolerances to high osmolarity, oxidation, cell wall stress, high temperature and UV ‐ B irradiation. All the deletion and deletion/knockdown mutants showed similar defects in blastospore yield and density, hyphal septation and cell size, hyphal responses to most chemical stresses and virulence. All the defects were evident with altered transcripts of phenotype‐related genes and well restored by each Bmh complementation. Our Bmh 1 ‐ and Bmh 2 ‐specific transcriptomes generated under osmotic and oxidative stresses revealed up to 6% genes differentially expressed by at least twofold in the fungal genome. Many of those were greatly depressed or co‐depressed in Δ Bmh 1 and Δ Bmh 2 . Our findings provide a thorough insight into the functions and complementary effects of the two 14‐3‐3 proteins in the filamentous entomopathogen.

The development process and seasonal changes of the gonad in Octopus ocellatus Gray off the coast of Qingdao, Northeast China - Weijun Wang; Gen Dong; Jianmin Yang; Xiaodong Zheng; Xiumei Wei; Guohua Sun (Fisheries Science, 2015)

Novel polymorphic microsatellites from Florida red tilapia and cross-species amplification in Mozambique and Nile tilapia - MUNGATH SANDEEP; FEI SUN; FENG LIU; JIAN LI; PIERRE BAL DAVID; GEN HUA YUE (Journal of Genetics, 2014)

Transcriptome sequencing and analysis of sweet osmanthus (Osmanthus fragrans Lour.) - Hong Na Mu; Huo Gen Li; Liang Gui Wang; Xiu Lian Yang; Tao Ze Sun; Chen Xu (Genes & Genomics, 2014)

The altitudinal belts of subalpine virgin forest on Mt. Gongga simulated by a succession model - Gen-wei Cheng; Jian Sun; Yu-kun Sha; Ji-hui Fan (Journal of Mountain Science, 2014)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Cytoplasmic diversity in Brassica rapa L. investigated by mitochondrial markers - Rui-Jie Zhang; Sheng-Wu Hu; Jin-Qiang Yan; Gen-Lou Sun (Genetic Resources and Crop Evolution, 2013)

Isolation and characterization of 17 polymorphic microsatellites in the brown mud mussel Glauconome rugosa - Fei Sun; Quanqi Zhang; Juraini Tan; Grace Lin; Gen Hua Yue (Conservation Genetics Resources, 2013)

The effects of molybdenum and boron on the rhizosphere microorganisms and soil enzyme activities of soybean - Ting Sun; Yue P. Wang; Zhi Y. Wang; Peng Liu; Gen D. Xu (Acta Physiologiae Plantarum, 2013)

Expression pattern of enzymes related to juvenile hormone metabolism in the silkworm, Bombyx mori L. - Yang Hua-jun; Zhou Fang; Sabhat Awquib; Firdose Ahmad Malik; Bhaskar Roy; Li Xing-hua; Hu Jia-biao; Sun Chun-guang; Yan-shan Niu; Miao Yun-gen (Molecular Biology Reports, 2011)

Expression of Trichoderma viride endoglucanase III in the larvae of silkworm, Bombyx mori L. and characteristic analysis of the recombinant protein - Xing-hua Li; Peng Zhang; Mei-xian Wang; Fang Zhou; Firdose Ahmad Malik; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2011)

Molecular cloning and functional characterization of genes associated with flowering in citrus using an early-flowering trifoliate orange (Poncirus trifoliata L. Raf.) mutant - Jin-Zhi Zhang; Xiao-Yan Ai; Lei-Ming Sun; Dong-Liang Zhang; Wen-Wu Guo; Xiu-Xin Deng; Chun-Gen Hu (Plant Molecular Biology, 2011)

Cloning and expression of a cellulase gene in the silkworm, Bombyx mori by improved Bac-to-Bac/BmNPV baculovirus expression system - Xing-hua Li; Dan Wang; Fang Zhou; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2010)

Identification of an aminopeptidase from the skeletal muscle of grass carp (Ctenopharyngodon idellus) - Li-Gen Zhou; Bing-Xin Liu; Le-Chang Sun; Kenji Hara; Wen-Jin Su; Min-Jie Cao (Fish Physiology and Biochemistry, 2010)

Conserved regulatory motifs at phenylethanolamine N-methyltransferase (PNMT) are disrupted by common functional genetic variation: an integrated computational/experimental approach - Juan L. Rodríguez-Flores; Kuixing Zhang; Sun Woo Kang; Gen Wen; Sajalendu Ghosh; Ryan S. Friese; Sushil K. Mahata; Shankar Subramaniam; Bruce A. Hamilton; Daniel T. O’Connor (Mammalian Genome, 2010)

Effect of floral morphology on fruit set in Epimedium sagittatum (Berberidaceae) - Yun-xiang Li; Qiu-mei Quan; Gen-lou Sun (Plant Systematics and Evolution, 2009)

Silkworm powder containing manganese superoxide dismutase regulated the immunity and inhibited the growth of Hepatoma 22 cell in mice - Wan-Fu Yue; Wen Deng; Xing-Hua Li; Bhaskar Roy; Guang-Li Li; Jian-Mei Liu; Xiao-Feng Wu; Hong-Xiang Sun; Min-Li Yao; Wan Chi Cheong David; Yun-Gen Miao (Molecular Biology Reports, 2009)

Manganese superoxide dismutase expressed in silkworm larvae, Bombyx mori L enhances the NK activity and splenocyte proliferation against Sarcoma 180 tumor cells in vivo - Wan-Fu Yue; Min-Li Yao; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Wen Deng; Hong-Xiang Sun; Ji-Yong Zhou; Chuan-Xi Zhang; Yun-Gen Miao (Molecular Biology Reports, 2009)

Effects of silkworm larvae powder containing manganese superoxide dismutase on immune activity of mice - Wan-Fu Yue; Jian-Mei Liu; Guang-Li Li; Xing-Hua Li; Xiao-Feng Wu; Jian-Tong Sun; Hong-Xiang Sun; Yun-Gen Miao (Molecular Biology Reports, 2008)

Impact of genetic polymorphisms of leptin and TNF-α on rosiglitazone response in Chinese patients with type 2 diabetes - Hai-Ling Liu; Yang-Gen Lin; Jing Wu; Hong Sun; Zhi-Cheng Gong; Ping-Cheng Hu; Ji-Ye Yin; Wei Zhang; Dan Wang; Hong-Hao Zhou; Zhao-Qian Liu (European Journal of Clinical Pharmacology, 2008)

Cytological and molecular characterization of a novel monogenic dominant GMS in Brassica napus L. - Dao-Jie Wang; Ai-Guang Guo; Dian-Rong Li; Jian-Hua Tian; Fei Huang; Gen-Lou Sun (Plant Cell Reports, 2007)

Foundation and application of background trend line of China’s inbound tourism - Gen-nian Sun (Chinese Geographical Science, 2000)

Levels and distribution of allozyme and RAPD variation in populations of Elymus fibrosus (Schrenk) Tzvel. (Poaceae) - Oscar Díaz; Gen-Lou Sun; Björn Salomon; Roland von Bothmer (Genetic Resources and Crop Evolution, 2000)